Catalytic enantioselective addition of Grignard reagents to aromatic silyl ketimines - Jiawei Rong (Nature Portfolio, 2016)
The stereoselective addition of Grignard reagents to ketimines is potentially a straightforward route to α-chiral amines. Here the authors report a catalytic, asymmetric Grignard addition to silyl ketimines, givingN-sulfonyl protected α-chiral silyl amines with tetrasubstituted stereocentres.